How the fear of COVID-19 changed the way we look at human faces - Federico, Giovanni; Ferrante, Donatella; Marcatto, Francesco; Brandimonte, Maria Antonella (PeerJ, 2021)
Do we look at persons currently or previously affected by COVID-19 the same way as we do with healthy ones? In this eye-tracking study, we investigated how participants (N = 54) looked at faces of individuals presented as “COVID-19 Free”, “Sick with COVID-19”, or “Recovered from COVID-19”. Results showed that participants tend to look at the eyes of COVID-19-free faces longer than at those of both COVID-19-related faces. Crucially, we also found an increase of visual attention for the mouth of the COVID-19-related faces, possibly due to the threatening characterisation of such area as a transmission vehicle for SARS-CoV-2. Thus, by detailing how people dynamically changed the way of looking at faces as a function of the perceived risk of contagion, we provide the first evidence in the literature about the impact of the pandemic on the most basic level of social interaction.
Keywords: COVID-19; Pandemic; Human faces; Eye contact; Visual attention; Social interaction; Social cognition; Eye-tracking; Face processing; Social brain